First Year Experience: How We Can Better Assist First-Year International Students in Higher Education - Yan, Zi; Sendall, Patricia (Journal of International Students, 2016)
While many American colleges and universities are providing a First Year Experience (FYE) course or program for their first year students, those programs are not often customized to take into account international students’ (IS) unique challenges. Using quantitative and qualitative methods, this study evaluated a FYE course that was customized for IS in a college setting. Nineteen IS and eight domestic students (DS) who attended FYE classes completed a survey; 18 of the 19 IS were interviewed. Overall, the FYE class was successful in terms of helping IS to familiarize themselves with academic resources and expectations, understanding American culture, making more American friends, and improving their English language skills. Suggestions for future integration of IS into FYE programs are discussed.